Odpowiedzi

2009-12-21T18:44:09+01:00
A) 3x+2y+13
2x+y=11/*(-2)
3x+2=13
-4x-2y=-22
-x=9/-1
x=-9

3x+2y=13/*2
2x+y=11/*(-3)
6x+4y=26
-6x-3y=-33
y=7

b)5x+3y=0
-x-2y=7/*5
5x+3y=0

-5x-10y=35
-7y=35
y=-5

)5x+3y=0/*2
-x-2y=7/*3
10x+6y=0
-3x-6y=21
7x=21
x=3

c) 3u + 2v = 2/*(-5)
5u + 4v = 6/*3
-15u-10v=-10
15u+12v=18
2v=8/:2
v=4

3u + 2v = 2/*(-2)
5u + 4v = 6
-6u-4v=-4
5u+4v=6
-u=2/:(-1)
u=-2
1 5 1
  • Itak
  • Rozwiązujący
2009-12-21T18:50:51+01:00
A) {3x + 2y=13
2x + y=11// razy(-2)

{3x + 2y=13
-4x-2y=-22
+_______________
-x=-9
x=9
y=11-2x
y=11-2 razy 9
y=11-18
y=-7

{x=9
y=-7

b){ 5x + 3y = 0
-x - 2y = 7

{5x + 3y = 0
-x - 2y=7// razy 5

{5x + 3y=0
-5x-10y=35
+___________

-7y=35
y=-5

-x=7+2y
-x=7+(-10)
-x=-3
x=3

{x=3
y=-5

c) { 3u + 2v = 2 // razy (-2)
5u + 4v = 6

{-6u -4v=-4
5u + 4v = 6
+_________
-u=2
u=-2

4v=6-5u
4v=6+10
4v=16
v=4

{u=-2
v=4
1 5 1